SEVERAL FACTORS THAT AFFECT CATTLE ROWING PATTERNS AS WELL AS THEIR CONTRIBUTION TO HOUSEHOLD INCOME (CASE STUDY OF LIVESTOCK FARMERS IN TAEBENU SUBDISTRICT, KUPANG REGENCY, NTT) - Salden E Nifu; Djoko Koestiono; Hery Toiba (Socio-Economics/Agribusiness Department, 2021)
This study aims to analyze several factors that affect cattle rowing patterns as well as their costs, receipts and contributions to the household income of livestock farmers in Taebenu Subdistrict, Kupang Regency, NTT. The research sample of 100 people was grouped into two groups: group I (50 row cattle farmers) and group II (50 non-row cattle farmers). Determination of the number of farmer samples follows slovin formula with random sampling method. Data on factors that influence the decisions of farmers' households are analyzed with binary logistics regression analysis. Meanwhile, the income of cattle farmers and non-rowdy cattle was analyzed by household income analysis. The results showed that the analysis of binary logistics regression using simultaneous tests showed that independent variables (X) namely X1, X2, X3, X4, X5, X6 significantly influenced dependent variables (Y). The average household income of cattle farmers rowdy pattern is Rp 13,327,080 with the contribution of income from the business of cattle rowing by 21.93%, while the average household income of non-rowdy cattle farmers (privately owned) Rp 12,820,488 with the contribution of income from non-row cattle businesses amounted to 22.93%. From the results of household income shows the household income of cattle farmers row pattern higher than the household income of non-row cattle farmers (privately owned).